Teaching multigrade classes - Montalbo, Imelda C.; Iradel, Charlo M.; Perez, Noremay B. (Quezon City : Lorimar Publishing, 2022)
This book is envisioned to be a useful reference material for both teacher education students and multigrade teachers who are already teaching in the field.
Chapter 1 History, Nature and Status of Multigrade Program 1 -- Chapter 2 Organizing and Managing a Multigrade Classroom 19 -- Chapter 3 Teaching in the Multigrade Classroom 42 -- Chapter 4 Assessment in Multigrade Classess 79 -- Chapter 5 Lesson Designing 93 -- Chapter 6 Research and Partnership in Multigrade Teaching 123 -- References 134.
Includes bibliographical references.
Keywords: PRIMARY EDUCATION (ELEMENTARY EDUCATION) -- WORKBOOK